Relationship between lactone ring forms of HCPT and their antitumor activities - Zhou Jian-Jun; Liu Jian; Xu Bin (Acta Pharmacologica Sinica, 2016)
Aim: To study the relationship between the lactone forms of 10-hydroxycamptothecin (HCPT) and their antitumor activities. Methods: Antitumor activity of the two forms of HCPT was studied in vitro using seven cultured human and mouse tumor cell lines. Mice bearing sarcoma 180 and solid hepatoma were treated with HCPT (0.5, 1, and 2 mg/kg, ip) and tumor growth inhibition was assayed. HPLC method was employed to investigate the conversion of two forms of HCPT in different pH conditions and cultured tumor cells. Results: It was found that both forms of HCPT (O-HCPT and C-HCPT) showed similar activities in vitro against a number of tumor cell lines at the same concentration; but C-HCPT was more effective (about two times) than O-HCPT in vivo. The difference between in vitro and in vivo results could be explained by the conversion of O-HCPT into C-HCPT in a certain condition, which was shown by the HPLC analysis of HCPT at different pH values and in cultured tumor cells. Conclusion: Both forms of HCPT were effective against tumor growth, but C-HCPT was more effective than O-HCPT, the latter could be converted into the former under certain conditions.